PERAN PENGHULU TERHADAP PELAKSANAAN PASAL 39 UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - Syamsurrizal, Entus; Sari, Yani Kurnia (Jurnal Bimas Islam, 2018)
Divorce is an important part of human life. When relationships are fostered through marriage cannot be maintained, divorce is permitted. Islamic law regulates marriage and divorce in quite detailed, Islamic jurists (fuqaha) argue if someone utters the words talak or others against his wife then the divorce is considered valid. Meanwhile, positive law (Law No. 1/1974 and PP. 9/1975 concerning the Implementation of Law No.1 / 1974 confirms that "Divorce is the husband's pledge before the Religious Court session which is one of the reasons for the breakup of marriage". In the middle of the community such as in the Carenang Sub-District, Serang Regency, the community is more referring to the divorce procedures of Islamic law, not before the court, in this case shows the effect of positive law enforcement which made to other violations of legal aspects, such as issuing a husband's death certificate or wife before. Perceraian merupakan bagian penting dalam kehidupan manusia. Ketika hubungan yang dibina melalui pernikahan tak bisa dipertahankan maka perceraian diperbolehkan. Hukum Islam mengatur pernikahan dan perceraian dengan cukup rinci, para ahli hukum Islam (fuqaha) berpendapat bahwa bila seseorang mengucapkan kata-kata talak atau semisalnya terhadap isterinya maka talaknya dianggap sah. Sementara itu, hukum positif (UU No.1/1974 dan PP.No. 9/1975 tentang Pelaksanaan UU No.1/1974 menegaskan bahwa ?Talak adalah ikrar suami di hadapan sidang Pengadilan Agama yang menjadi salah satu sebab putusnya perkawinan?. Di tengah masyarakat seperti di Kecamatan Carenang, Kabupaten Serang, masyarakat lebih merujuk pada tata cara perceraian hukum Islam, tidak di depan sidang pengadilan. Pada masalah ini menunjukkan adanya efek dari pemberlakukan hukum positif yang melahirkan perilaku pelanggaran aspek hukum yang lain, seperti menerbitkan surat kematian suami atau istri sebelumnya